2012
DOI: 10.1210/jc.2011-2186
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Levels of Sclerostin Are Increased in Patients with Type 2 Diabetes Mellitus

Abstract: Circulating sclerostin is increased in T2DM independently of gender and age. Serum sclerostin is also correlated with duration of T2DM, glycated hemoglobin, bone turnover markers, and BMD in T2DM patients. Additional studies are needed to evaluate the role of sclerostin on bone metabolism in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

25
176
9
15

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 288 publications
(225 citation statements)
references
References 35 publications
25
176
9
15
Order By: Relevance
“…Interestingly, sclerostin levels are increased in diabetes and can be regulated by GLP-1 agonists (6,35). We show here that Ex-4 treatment reduces serum sclerostin in mice.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Interestingly, sclerostin levels are increased in diabetes and can be regulated by GLP-1 agonists (6,35). We show here that Ex-4 treatment reduces serum sclerostin in mice.…”
Section: Discussionmentioning
confidence: 57%
“…Clinical data indicate that bone of diabetic patients is fragile and of poor quality, despite a bone mineral density (BMD) that is often normal. Circulating levels of sclerostin, a negative regulator of bone formation produced by osteocytes, are elevated in type 2 diabetic patients (6).…”
Section: Introductionmentioning
confidence: 99%
“…In patients with T2DM, the increase of serum sclerostin is associated with a significant decrease in the b-catenin serum concentration, suggesting, indeed, that sclerostin signaling is modulated in diabetes (31). On one hand, this gives support to the hypothesis that bone, which produces almost all the available sclerostin, may play a role also in glucose metabolism and insulin resistance (8,32,35). On the other hand, it can be speculated that anti-sclerostin antibody treatment, which is a promising option for severe osteoporosis and surgical implant fixation, might have a role in T2DM treatment (36).…”
Section: Discussionmentioning
confidence: 64%
“…In a small recent study evaluating a group of healthy offspring of patients with T2DM, serum sclerostin levels were consistently correlated with FPG, although they were not correlated with 2-h PG (30). Another study demonstrated that compared with healthy controls, circulating levels of sclerostin were increased in patients with T2DM, positively associated with duration of T2DM and glycated hemoglobin, and inversely related to bone turnover markers (31,32). Similarly, serum sclerostin levels were elevated in subjects with type 1 diabetes compared with normal control subjects and correlated with HbA 1c (33).…”
Section: Discussionmentioning
confidence: 96%
“…Finally, our data suggest that Wnt targeted therapeutics might have a beneficial impact on metabolism. The increased levels of circulating sclerostin, a bone-derived inhibitor of Wnt signaling (77), in metabolic diseases (78)(79)(80) suggest that therapies designed to increase bone mass by targeting sclerostin (81,82) might also impact circulating lipid levels. To date, body composition has not been a major endpoint in the studies designed to examine antisclerostin agents as a bone anabolic therapy.…”
Section: Discussionmentioning
confidence: 99%